Determinasi Job Hopping Gen Z Yogyakarta: Gaji, Pertumbuhan Karier dan Kepuasan Kerja - Vani Oktafiani; Yondik Army Pratama; Miswanto Miswanto; Baldric Siregar; Frasto Biyanto (Penerbit Goodwood, 2025)
Purpose: The purpose of this research is to analyze how market competitive pay, career growth, and job satisfaction affect the job-hopping intentions of Generation Z employees in Yogyakarta. Methodology/approach: This study utilized a quantitative method with purposive sampling. A total of 104 Generation Z respondents filled out an online questionnaire, and the data were processed using multiple linear regression through SPSS 25. Results/findings: The findings indicate that market competitive pay, career growth, and job satisfaction collectively exert a significant influence on job-hopping intentions. However, market competitive pay and job satisfaction show a negative influence, meaning higher levels of both reduce the tendency to job hop. Interestingly, career growth has a positive effect, indicating that greater perceived opportunities for advancement can increase job-hopping intentions when expectations are not met internally. Conclusion: Career growth can motivate Gen Z employees to pursue external opportunities if their current organization lacks clear advancement paths. Meanwhile, competitive pay and job satisfaction can reduce the desire to job hop, making them essential components of effective retention strategies. Limitations: This study is limited by a short data collection period of only one month. This may lead to temporal bias and restrict the depth of analysis, so the findings should be interpreted with caution and not generalized without considering longer-term dynamics. Contribution: This study highlights the need for companies to integrate fair compensation, transparent career development plans, and job satisfaction strategies to retain young employees effectively, particularly in competitive job markets.